Investigating the role of diamagnetic Cd2+ ions on the structural, optical, and magnetic properties of YIG. (14th May 2021) - Assi, B; Bitar, Z; Malaeb, W; Sayed Hassan, R; Yaacoub, N; Awad, R
Abstract: In this study, Y3-x Cdx Fe5 O12 (0.0 ≤ × ≤0.2) powders were synthesized via the co-precipitation method at calcination temperature 1100 °C. The phase formation of YIG was confirmed from X-ray powder diffraction (XRD) and Fourier Transform Infrared (FTIR) technique. The change of the band-gap energy, determined from the analysis of UV-visible spectroscopy, with the particle size was in agreement with the quantum confinement effect for x between 0.02 and 0.2. The magnetization study showed a non-monotonic change in the saturation magnetization and the coercivity with the increase of Cd 2+ content. This behavior is an indication of both effect of particle size and the concentration of the doped Cadmium. The Mӧssbauer spectroscopy analysis confirmed the existence of Fe 3+ in both octahedral and tetrahedral sites and the non-existence of Fe 2+ .